Developing a core outcome set for interventions to improve discharge from mental health inpatient services: a survey, Delphi and consensus meeting with key stakeholder groups. Issue 5 (12th May 2020) - Tyler, Natasha; Wright, Nicola; Grundy, Andrew; Waring, Justin
Abstract : Objective: To develop a core set of outcomes to be used in all future studies into discharge from acute mental health services to increase homogeneity of outcome reporting. Design: We used a cross-sectional online survey with qualitative responses to derive a comprehensive list of outcomes, followed by two online Delphi rounds and a face-to-face consensus meeting. Setting: The setting the core outcome set applies to is acute adult mental health. Participants: Participants were recruited from five stakeholder groups: service users, families and carers, researchers, healthcare professionals and policymakers. Interventions: The core outcome set is intended for all interventions that aim to improve discharge from acute mental health services to the community. Results: Ninety-three participants in total completed the questionnaire, 69 in Delphi round 1 and 68 in round 2, with relatively even representation of groups. Eleven participants attended the consensus meeting. Service users, healthcare professionals, researchers, carers/families and end-users of research agreed on a four-item core outcome set: readmission, suicide completed, service user-reported psychological distress and quality of life. Conclusion: Implementation of the core outcome set in future trials research will provide a framework to achieve standardisation, facilitate selection of outcome measures, allow between-study comparisons and ultimately enhance the relevance of trial or research findings to healthcare professionals, researchers, policymakers and service users.